Viscosity-induced crossing of the phantom divide in the dark cosmic fluid - Brevik, Iver H. (Frontiers in Physics, 2013)
Choosing various natural forms for the equation-of-state parameter w and the bulk viscosity ζ, we discuss how it is possible for a dark energy fluid to slide from the quintessence region across the divide w=-1 into the phantom region, and thus into a Big Rip future singularity.